The Establishment of New Thresholds for PLND-Validated Clinical Nomograms to Predict Non-Regional Lymph Node Metastases: Using 68Ga-PSMA PET/CT as References - Jiao, Jianhua; Quan, Zhiyong; Zhang, Jingliang; Wen, Weihong; Qin, Jun; Yang, Lijun; Meng, Ping; Jing, Yuming; Ma, Shuaijun; Wu, Peng; Han, Donghui; Davis, Andrew A.; et al. (Frontiers in Oncology, 2021)
Purpose: PLND (pelvic lymph node dissection) -validated nomograms are widely accepted clinical tool to determine the necessity of PLND by predicting the metastasis of lymph nodes (LNs) in pelvic region. However, these nomograms are in lacking of a threshold to predict the metastasis of extrareolar lymph nodes beyond pelvic region, which is not suitable for PLND. The aim of this study is to evaluate a threshold can be set for current clinical PLND-validated nomograms to predict extrareolar LN metastases beyond pelvic region in high-risk prostate cancer patients, by using 68Ga-PSMA PET/CT as a reference to determine LN metastases (LNMs). Experimental Design: We performed a retrospective analysis of 57 high-risk treatment-naïve PC patients in a large tertiary care hospital in China who underwent 68Ga-PSMA-617 PET/CT imaging. The pattern of LN metastatic spread of PC patients were evaluated and analyzed. The impact of 68Ga-PSMA PET/CT on clinical decisions based on three clinical PLND-validated nomograms were evaluated by a multidisciplinary prostate cancer therapy team. The diagnostic performance and the threshold of these nomograms in predicting extrareolar LNMs metastasis were evaluated via receiver operating characteristic (ROC) curve analysis. Results: LNMs were observed in 49.1% of the patients by 68Ga-PSMA PET/CT, among which 65.5% of LNMs were pelvic-regional and 34.5% of LNMs were observed in extrareolar sites. The thresholds of nomograms to predict non-regional LNMs were between 64% and 75%. The PC patients with a score >64% in Briganti nomogram, a score >75% in MSKCC nomogram and a score >67% in Winter nomogram were more likely to have non-regional LNMs. The AUCs (Area under curves) of the clinical nomograms (Briganti, MSKCC and Winter) in predicting non-regional LNMs were 0.816, 0.830 and 0.793, respectively. Conclusions: By using 68Ga-PSMA PET/CT as reference of LNM, the PLND-validated clinical nomograms can not only predict regional LNMs, but also predict non-regional LNMs. We focused on that a threshold can be set for current clinical PLND-validated nomograms to predict extrareolar LN metastases with an AUC accuracy of about 80% after optimizing the simple nomograms which may help to improve the efficiency for PC therapy significantly in clinical practice.